Reciprocal and wage labor in indigenous communities: The case of the Kichwa and the Shuar of the Ecuadorian Amazon - Vasco, Cristian (2018)
Reciprocal work has traditionally been the way in which indigenous populations accessed labor force for agricultural tasks. However, this exchange system is currently under risk due to the indigenous peoples’ accelerated process of integration into the market economy. With data from a household survey, this study analyzes the motivations to participate in reciprocal labor schemes and to hire paid wage labor by indigenous peoples in the Ecuadorian Amazon. The results of multivariate analyses show that households that participate more in reciprocal work are those which have more marginal labor force (women and children) and reside faraway urban areas. In contrast, households that receive non-agricultural income and have more land devoted to cash crops use more hired labor force for agricultural tasks.